AVALIAÇÃO DE EQUIPAMENTOS HIDROSSANITÁRIOS DE USO PÚBLICO - Cureau, Roberta Jacoby; Gonçalves, Felipe; Defaveri, Daiele; Andreza Kalbusch; Ramos, Doalcey Antunes (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
Water for human consumption in building systems is susceptible to various forms of wasting. Sometimes, water misuse is a result of the end of lifetime of plumbing fixtures and their lack of maintenance. This paper presents the operation conditions of plumbing fixtures in two public buildings in Joinville. It was detected that 87.0% of toilets and urinals have presented leakage and 9.0% of those plumbing fixtures also presented their flush valves leaking when pushed. Taps did not present any constant dripping, however, 52.0% of them showed valve leakage when the flow was activated. Moreover, 63.8% of taps were in regular or bad visual conditions.